2015
DOI: 10.1136/bmjopen-2015-008975
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal cohort study describing persistent frequent attenders in Australian primary healthcare

Abstract: ObjectivesTo describe patterns of frequent attendance in Australian primary care, and identify the prospective risk factors for persistent frequent attendance.Design, setting and participantsThis study draws on data from the Personality and Total Health (PATH) Through Life Project, a representative community cohort study of residents from the Canberra region of Australia. Participants were assessed on 3 occasions over 8 years. The survey assessed respondents’ experience of chronic physical conditions, self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 26 publications
9
70
1
1
Order By: Relevance
“…21.0% of patients identified as FAs made no out-of-pocket payment for any of their consultations. Consistent with our previous findings, [2,31] FA status was associated with diabetes, number of life events, low income, lower educational achievement, anxiety, depression, cholesterol, and pain medication use as evidenced in the regression models and preliminary analyses. Some demographics are presented in Table 1 while demographics across payment levels are presented in Supplemental Table 1.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 3 more Smart Citations
“…21.0% of patients identified as FAs made no out-of-pocket payment for any of their consultations. Consistent with our previous findings, [2,31] FA status was associated with diabetes, number of life events, low income, lower educational achievement, anxiety, depression, cholesterol, and pain medication use as evidenced in the regression models and preliminary analyses. Some demographics are presented in Table 1 while demographics across payment levels are presented in Supplemental Table 1.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…Hence, there was a 12month observation period for all participants but these could have different starting points. The analysis considers a comprehensive list of relevant GP Medicare item numbers (see [2]) representing all face-to-face Medicare services delivered by a GP. A cut-point was applied to…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We could not confirm this finding in this study. Smits et all ( 2009) and Pymont and Butterworth (2015) reported that persistent FAs used analgesic medication more often than one-year FAs, but the indication for pain medication was not specified [6,11]. We found out that pFAs had more back pain, but we did not have information about prescriptions of our study group.…”
Section: Discussionmentioning
confidence: 76%